Long-term monitoring reveals the impact of changing climate and habitat on the fitness of cavity-nesting songbirds. (February 2023) - Riggio, Jason; Engilis, Andrew; Cook, Hanika; de Greef, Evelien; Karp, Daniel S.; Truan, Melanie L.
Abstract: Long-term studies on the impacts of global change on reproduction are rare, even though reproductive output can respond more quickly than species' abundances or distributions. We explore the influences of habitat use and weather on fitness, by using an 11-year dataset of 2305 nesting attempts (7174 nestlings) across four species of cavity-nesting songbirds within California's Central Valley. Specifically, we modeled relationships between habitat type, maximum nesting season temperature, and winter/nesting season precipitation and nest site selection, reproductive success, and nestling weight for each species. We found that species selected nest sites based on species-specific habitat variables and that reproductive success and nestling weight peaked in selected habitats, suggesting an absence of ecological traps. Higher maximum nesting season temperatures were negatively associated with clutch size, reproductive success, and nestling weight for all species. For example, models predicted that the probability of successfully fledging tree swallows declined by 39 % and tree swallow nestling weight declined by 19 % when nests experienced the hottest versus the coolest maximum temperatures. In contrast, the effects of precipitation on reproductive outcomes varied by species and timing. We observed strong negative associations between nesting season precipitation and reproductive success/nestling weight in tree swallows and western bluebirds. Our findings suggest that, while habitat conversion to orchards has not resulted in ecological traps, predicted increases in temperature and spring precipitation may reduce the fitness of cavity-nesting songbirds in California. More broadly, our results highlight the importance of long-term monitoring when unravelling impacts of global change on fitness.